The Role of Nutrition in Supporting Physical and Motor Development in Early Childhood - Maromi, Choirul; Hasibuan, Rahma (Journal of Islamic Education Students (JIES), 2025)
Early childhood (ages 0ÔÇô6) represents a critical period for multidimensional development that significantly influences long-term quality of life. This study aims to examine the role of nutritional intake in supporting physical and motor development in early childhood, particularly fine and gross motor skills. A mixed-methods approach was employed, integrating both quantitative and qualitative data. The participants consisted of 30 children aged 3ÔÇô5 years from Al-Ikhsan Islamic Kindergarten and Playgroup in Sidoarjo, Indonesia. The findings revealed that a balanced nutritional intakeÔÇöespecially diets rich in vegetables, fruits, and proteinsÔÇöhad a significant positive correlation with the childrenÔÇÖs physical and motor development. These results highlight the critical role of appropriate nutritional interventions during early life stages as a foundation for optimal motor development. The study implies the necessity of strengthening nutrition education for parents and early childhood education institutions as part of a holistic strategy to support childrenÔÇÖs growth and development.┬á